A STUDY ON PROBLEMS PERCEIVED BY FISHERY EXTENSION OFFICERS OF ASSAM AND WEST BENGAL - Pathak, P. K.; Sharma, Arpita; Ambulkar, Rashmi; Ghosh, Amitava (Journal of Indian Fisheries Association, 2014)
A study was conducted regarding the problems perceived by Fishery Extension Officers (FEOs) of Assam and West Bengal (W.B.) as these are two important fishery states of India. The objectives of the study were to assess the profile of FEOs, to prepare an index for the problems perceived by FEOs and to assess whether the FEOs were in conformity as regarding the perception of problems. The problems perceived by the FEOs could be classified under different heads namely administration, finance, infrastructure, psycho-social, extension and psychological. For FEOs of Assam, finance related problems ranked first followed by administrative and infrastructure related problems. Finance related problems included issues like late salaries, irregular payment of travel and dearness allowance, disparity in pay scales etc. For FEOs of W.B., administration related problems like late promotion and transfer problems rated high. However, FEOs reported that they are satisfied with the job as it provides opportunity to help the farmers as well as the security of a state government job. Â Key words: Fishery extension officers (FEOs), Assam, West Bengal, extension. Â